Рефлексивы в прусском языке - Geniušienė, Ema (Baltistica, 1981)
Reflexives in Old PrussianThis paper deals with the derivational history of Old Prussian reflexives and their syntactic and semantic properties. The reflexives fall into three semantic classes: reflexives proper, self-move and dative reflexives.
Keywords: prūsų; 3 asmuo; semantika